Anglo French Trade Union Council, 1945 (1945)
1945 1945-1960 "Anglo French Trade Union Council, 1945" [HFR0122], 1945 The Council was set up in 1939 to discuss matters relating to the war, but was abandoned following the Nazi invasion of France. Following the liberation of France, a delegate from the Confederation Generale de Travail [CGT] attended the 1944 TUC Congress and it was agreed to re-establish the Council. This photograph show a meeting of the Council held in Transport House in December 1945 and includes Leon Jouhaux, Robert Bothereau, Eugene Ahlers, G. Bagnall, Walter Citrine, Walter Schevenels, A. Conley and Ebby Edwards.